The Implementation of the Tutoring Program in SABI Village and a Parent Seminar to Improve Students’ Academic Achievement - Kurniawati Martha; Edelin Nery Malaifani; Rosma Indriana Purba; Maya Puspitasari Izaak; Henni Sitompul; Yohanes Edi Gunanto (LOSARI DIGITAL, 2026)
Educational challenges in Kampung Sabi, Bencongan, Tangerang are characterized by students’ limited understanding of fundamental concepts in Mathematics and Science, as well as low parental involvement due to socio-economic constraints and low levels of educational attainment. This community service program aimed to improve students’ academic achievement and strengthen parental engagement through a participatory approach. The program included twice-weekly onsite tutoring for approximately 40 students from elementary to secondary levels, facilitated by Teachers College students, and parent seminars conducted through structured discussions and guided activities. The results showed improved student learning outcomes, reflected in higher post-test scores, improved report card performance, and increased learning motivation. Parental participation also increased, as seen in stronger academic support and more effective communication. These findings indicate that collaboration among students, parents, and tutors can sustainably improve educational quality.